Maldives : Public Expenditure Review - World Bank (2013)
The unifying theme of the public expenditure review is the growth and poverty focus of public expenditures, evolving around the question of how effective public expenditures are in addressing Maldives' overriding objective of reducing regional disparities and income poverty, particularly in the outer atolls. Since macroeconomic stability is a key prerequisite for sustained high economic growth and poverty reduction, the soundness of the fiscal framework and the issues of fiscal sustainability and contingent liabilities are examined in Chapter 2. The latter chapter also looks at the allocation of public expenditures along the key economic categories as well as by major sectoral/functional break-down, with specific recommendations for reform measures. Chapter 3 focuses on the institutional issues and challenges faced in public expenditure management, including the coordination of decision making and budgeting, planning and service delivery, and monitoring and evaluation. Sectoral allocations of public expenditures are evaluated in Chapter 4, with particular focus on education, health, and infrastructure. Sectoral public expenditures are evaluated in terms of their rationale for public sector intervention; determining the appropriate instrument for achieving technical efficiency; and their impacts/outcomes. Chapter 5 concludes by summing up overall reform priorities and discussing planned next steps and follow-up support activities to implement recommendations.